2017
DOI: 10.1007/s00572-017-0767-y
|View full text |Cite
|
Sign up to set email alerts
|

Does warming by open-top chambers induce change in the root-associated fungal community of the arctic dwarf shrub Cassiope tetragona (Ericaceae)?

Abstract: Climate change may alter mycorrhizal communities, which impact ecosystem characteristics such as carbon sequestration processes. These impacts occur at a greater magnitude in Arctic ecosystems, where the climate is warming faster than in lower latitudes. Cassiope tetragona (L.) D. Don is an Arctic plant species in the Ericaceae family with a circumpolar range. C. tetragona has been reported to form ericoid mycorrhizal (ErM) as well as ectomycorrhizal (ECM) symbioses. In this study, the fungal taxa present with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 84 publications
2
31
3
Order By: Relevance
“…Mycena species may be particularly adapted to exploit different nutritional modes in arctic and alpine areas. Interestingly, Mycena have been recovered in high abundances from plant roots at higher latitudes (Blaalid et al , 2012; Botnen et al , 2014; Lorberau et al , 2017). This could suggest that environmental stress as a result of extreme climatic conditions in cold and nutrient‐limited environments may have provided a selective evolutionary pressure facilitating the ability of fungal partners to invade roots and, furthermore, that these harsh conditions may drive a stronger selection pressure for specialization or niche shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Mycena species may be particularly adapted to exploit different nutritional modes in arctic and alpine areas. Interestingly, Mycena have been recovered in high abundances from plant roots at higher latitudes (Blaalid et al , 2012; Botnen et al , 2014; Lorberau et al , 2017). This could suggest that environmental stress as a result of extreme climatic conditions in cold and nutrient‐limited environments may have provided a selective evolutionary pressure facilitating the ability of fungal partners to invade roots and, furthermore, that these harsh conditions may drive a stronger selection pressure for specialization or niche shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Using damaged or moribund hair roots, thicker suberized roots that typically lack rhizodermis (see Fig. 1 in Hamim et al 2017 ) as well as hair root clumps or “fine root threads” (see Lorberau et al 2017 ) favors growth of non-ErM fungi and is therefore discouraged. That said, the distribution of different mycobionts within the ericoid root system as affected by root age/diameter/order is poorly understood (cf.…”
Section: Methodological Guidementioning
confidence: 99%
“…Newell andFell 1982 andVohník et al 2016b). For example, Lorberau et al (2017) investigated Cassiope tetragona root samples that were not serially washed or surface-sterilized and reported that the detected mycobiont communities were "dominated by fungal groups in the Basidiomycota traditionally classified as either saprotrophic or EcM symbionts," while only a minor part "could be annotated as ErM-forming fungi". The lack of appropriate root selection and surface treatment casts doubts as to whether C. tetragona might really be "forming mycorrhizal symbioses with typically EcM-forming fungi," as hypothesized by Lorberau et al (2017).…”
Section: Things To Considermentioning
confidence: 99%
“…Consequently, there is also substantial debate over which sequence similarity level gives the biologically most meaningful units (see references above). Typically, clustering thresholds in the range 95%–99% are used in microbial studies (Bonito et al., ; Geml et al., ; Lorberau et al., ; Nemergut et al., ; Vik et al., ). Several studies have addressed the performance of clustering algorithms, including choice of clustering thresholds, in alpha diversity (species richness) estimation (e.g., Koeppel & Wu, ; Tikhonov et al., ; Yamamoto & Bibby, ), while the relationship between OTU similarity thresholds and patterns of beta diversity (compositional turnover) has so far been addressed in few studies (Bik, Halanych, Sharma, & Thomas, ; Frøslev et al., ; Koeppel & Wu, ; Lekberg, Gibbons, & Rosendahl, ).…”
Section: Introductionmentioning
confidence: 99%